2010
DOI: 10.1111/j.1365-2109.2009.02473.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic effect of Bacillus NL110 and Vibrio NE17 on the survival, growth performance and immune response of Macrobrachium rosenbergii (de Man)

Abstract: Eight hundred and eighty-¢ve strains of bacterial isolates from various samples associated with the natural habitat of Macrobrachium rosenbergii were screened for their probiotic potential. Two putative probionts namely Bacillus NL110 and Vibrio NE17 isolated from the larvae and egg samples, respectively, were selected for experimental studies and were introduced to the juveniles of M. rosenbergii (0.080 AE 0.001g) through di¡erent modes such as through feed, water and both. The probiotic potential of the abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(26 citation statements)
references
References 81 publications
3
22
0
1
Order By: Relevance
“…However, the increased activity of amylase and protease in the dietary B. pumilus groups may have led to higher digestion and absorption of nutrients(Ziaei- Nejad et al, 2006), then the growth performance of M. rosenbergii may have been improved. Furthermore, studies in zebra fish, Danio rerio, demonstrated that some probiotics, for example Lactobacillus rhamnosus, could modulate the transcription of genes related to the differentiation and maturation of some tissues, thereby enhancing the growth of the animals(Avella et al, 2012;Gioacchini et al, 2011;Maradonna et al, 2013).The immune indices, including phagocytic activities and RBs activity, and the enzyme activity of PO, CAT, ACP and NOS were all significantly higher in all dietary B. pumilus groups than in the control group, and a higher survival rate was induced by dietary B. pumilus.Similar results have been observed in M. rosenbergii fed with other probiotics, such as Vibrio NE17(Rahiman, Jesmi, Thomas, & Hatha, 2010), Bacillus licheniformis(Kumar et al, 2013) and L. plantarum(Dash et al, 2016). A significant increase in immune indices caused by dietary B. pumilus was also reported in Nile tilapia (Oreochromis niloticus)(Srisapoome & Areechon, 2017) and striped catfish (Pangasianodon hypophthalmus)(Truong Thy et al, 2017).Hemocytes play a vital role in phagocytosis, nodule formation, encapsulation, hemocyte clumping, production of microbicidal compounds, mediation of cytotoxicity and so on(Johansson, Keyser, Sritunyalucksana, & Söderhäll, 2000;Smith, Brown, & Hauton, 2003), all of which have been proven to be an important part of the innate immunity of crustaceans.…”
supporting
confidence: 87%
“…However, the increased activity of amylase and protease in the dietary B. pumilus groups may have led to higher digestion and absorption of nutrients(Ziaei- Nejad et al, 2006), then the growth performance of M. rosenbergii may have been improved. Furthermore, studies in zebra fish, Danio rerio, demonstrated that some probiotics, for example Lactobacillus rhamnosus, could modulate the transcription of genes related to the differentiation and maturation of some tissues, thereby enhancing the growth of the animals(Avella et al, 2012;Gioacchini et al, 2011;Maradonna et al, 2013).The immune indices, including phagocytic activities and RBs activity, and the enzyme activity of PO, CAT, ACP and NOS were all significantly higher in all dietary B. pumilus groups than in the control group, and a higher survival rate was induced by dietary B. pumilus.Similar results have been observed in M. rosenbergii fed with other probiotics, such as Vibrio NE17(Rahiman, Jesmi, Thomas, & Hatha, 2010), Bacillus licheniformis(Kumar et al, 2013) and L. plantarum(Dash et al, 2016). A significant increase in immune indices caused by dietary B. pumilus was also reported in Nile tilapia (Oreochromis niloticus)(Srisapoome & Areechon, 2017) and striped catfish (Pangasianodon hypophthalmus)(Truong Thy et al, 2017).Hemocytes play a vital role in phagocytosis, nodule formation, encapsulation, hemocyte clumping, production of microbicidal compounds, mediation of cytotoxicity and so on(Johansson, Keyser, Sritunyalucksana, & Söderhäll, 2000;Smith, Brown, & Hauton, 2003), all of which have been proven to be an important part of the innate immunity of crustaceans.…”
supporting
confidence: 87%
“…There are several studies demonstrating the positive effects of probiotics Bacillus spp. on the growth of M. rosenbergii (Keysami et al., ; Kumar et al., ; Mujeeb Rahiman, Jesmi, Thomas, & Mohamed Hatha, ; Seenivasan, Radhakrishnan, Muralisankar, & Saravana Bhavan, ). For instance, Kumar et al.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies demonstrating the positive effects of probiotics Bacillus spp. on the growth of M. rosenbergii(Keysami et al, 2012;Kumar et al, 2013;Mujeeb Rahiman, Jesmi, Thomas, & Mohamed Hatha, 2010;Seenivasan, Radhakrishnan, Muralisankar, & Saravana Bhavan, 2016). For instance,Kumar et al (2013) showed that dietary Bacillus licheniformis addition at 1 × 10 9 cfu/g significantly improved the growth performance in M. rosenbergii juveniles after 60 days of feeding.…”
mentioning
confidence: 96%
“…Presence of E. coli in the gut of control prawn (10 -4 , ViBact*, Bini it TM and Biogen® incorporated diets [4][5][6][7][8][9][10][11][12][13][32][33][34][35][36][37][38][39][40][41][42]. Similarly, the dietary administration of Lactobacillus plantarum, Bacillus sp., and C. butyricum also produced a signi icant improvement in growth, carcase biochemical constituents, and activities of digestive enzymes in shrimps, Litopenaeus vannamei and Marsupenaeus japonicas [12,[43][44][45][46].…”
Section: Gut Microbial Populationmentioning
confidence: 99%